2021
DOI: 10.3390/met11050674
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics Modelling of Ultrasonic Melt Treatment in the Hot-Top and Launder during Direct-Chill Casting: Path to Indirect Microstructure Simulation

Abstract: This study concerns the numerical simulation of two competing ultrasonic treatment (UST) strategies for microstructure refinement in the direct-chill (DC) casting of aluminium alloys. In the first, more conventional, case, the sonotrode vibrating at 17.3 kHz is immersed in the hop-top to treat the sump melt pool, in the second case, the sonotrode is inserted between baffles in the launder. It is known that microstructure refinement depends on the intensity of acoustic cavitation and the residence time of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…4 a (vii). This is in very good agreement with recent investigation by Beckwith et al [3] , where it was shown that the effective residence time in a real case scenario of UST performed in direct-chill casting launder was close to 100 ms meaning that every fragment should essentially recirculate almost 50 times before moving downstream towards a hot top mould. Therefore, the synergy of strong collapses inside the cavitation zone and adjacent to the sonotrode-tip, in conjunction with the rapid collision of fragments with the bubble cloud may lead to crystal breakage after few acoustic cycles.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…4 a (vii). This is in very good agreement with recent investigation by Beckwith et al [3] , where it was shown that the effective residence time in a real case scenario of UST performed in direct-chill casting launder was close to 100 ms meaning that every fragment should essentially recirculate almost 50 times before moving downstream towards a hot top mould. Therefore, the synergy of strong collapses inside the cavitation zone and adjacent to the sonotrode-tip, in conjunction with the rapid collision of fragments with the bubble cloud may lead to crystal breakage after few acoustic cycles.…”
Section: Resultssupporting
confidence: 92%
“…The majority of the fragments of sizes<100 μm produced after 9 sec of treatment, were more likely to be the result of delamination and breakage of the fractured crystal surface, as observed in Fig. 6 f. The results indicate that the effective treatment time of intermetallics within the active fragmentation zone (defined in section 3.1) in water medium should be in the range of 10–15 sec which coincides well with the time required for efficient intermetallic fragmentation upon casting of Al alloys [3] , [33] . It is important to note here that in a real casting processes, the choice of effective treatment time will also depend on the process scale dimensions and various other important factors such as casting speed, horn dimension etc.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…At the point of collapse, extreme temperatures [3] and pressures [4] occur. Traditionally, UST experiments induce sound waves using an immersed mechanical sonotrode operating at low ultrasonic frequencies (17)(18)(19)(20). This technique induces strong pressure waves, which are nevertheless attenuated rapidly away from the sonotrode tip due to intense inertial cavitation and gas shielding.…”
Section: Introductionmentioning
confidence: 99%